ENHANCING FINANCIAL STRATEGIES IN PUBLIC PROCUREMENT - Ulugbek Abdumajitov (Western European Studies, 2024)
Public procurement plays a vital role in government operations by ensuring the efficient acquisition of goods, services, and infrastructure. Effective financial strategies are essential to optimize procurement processes, enhance transparency, and maximize the value of public funds. This article explores strategies for enhancing financial strategies in public procurement, focusing on the implementation of advanced financial management tools and transparencyenhancing measures. Using insights from case studies and best practices, particularly from the experience of the Metallurgical Combine of Uzbekistan, the study identifies key challenges and proposes recommendations to improve procurement efficiency and regulatory compliance. The findings underscore the importance of modernizing financial mechanisms to achieve cost savings, improve resource allocation, and uphold integrity in public procurement practices.
Keywords: Public Procurement; financial processes; metallurgical combine